Procesos de acreditación de la calidad en la Carrera de Enseñanza del inglés para I y II ciclos en la UNED: fortalezas y compromisos de mejoramiento (Revista Electrónica Calidad en la Educación Superior, 2021)
Processes of quality accreditation in the English Major for I and II cycles at UNED: strengths and commitment to improvementAbstractThe quality of higher education is a matter that should bring together all possible actors, committed to the objective of providing the most effective and updated tools in terms of education so that versatile professionals are trained and able to contribute to the building of a more just, democratic, and inclusive society.The university should always ensure and systematize processes of self-assessment and in the case of processes that result in university degrees, ensure their accreditation.The purpose of this article is in one hand, to describe the processes that the UNED has undergone in order to achieve accreditation from SINAES for their university degree programs and, on the other hand, systematize the actions taken by the English Major regarding those processes; its strengths and commitment to improvement.
Keywords: self-assessment; accreditation; ongoing improvement; quality; strengths; commitment